Efficacy of fungicides against brown spot on walnuts in the Western Forest-Steppe of Ukraine - Skoreyko, A.; Andriychuk, T.; Bilyk , R. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2020)
Goal. To study the effectiveness of fungicides against brown spot of walnut in the Western Forest-Steppe of Ukraine. Methods. The studies were carried out during 2018—2019. in agrocenoses of the walnut garden of the Ukrainian Research Station of Plant Quarantine of the Institute of Plant Protection of the NAAS. At the detailed account inspected not less than 3—4 accounting trees from four parties of a crown and analyzed on 25 accounting bodies (leaves, shoots, fruits) and determined intensity of defeat. The study of the effectiveness of fungicides against brown spot was carried out on the nut variety Bukovynsky 2 using drugs: Bordeaux liquid, 1-percent solution — the standard; Kuproksat, s. c., (copper sulphate tribasic, 345 g/l), Medyan Extra 350 SC s. c., (copper chloride, 350 g/l). Results. Defeat of leaves at the last account in variants with the drug Medyan Extra 350 SC s. c., decreased in comparison with control in 2.6 times, development of a disease — in 2.8 times. By all indicators, the variant with the drug Kuproksat, hp was more effective, where the brown leaf spot was 20.5% (64.5% in the control), the disease was 9.3% (31.4% in the control). Fetal damage in the last account in the experimental variants was respectively 2.7—3.9 times less, and the development of the disease — 3.1—4.2 times weaker than in the control. Conclusions. The obtained data show that in the conditions of the western Forest-Steppe of Ukraine the application of fungicides on walnut both in the experimental and in the reference variants provided good and approximately identical protection of the nut against brown spot Ophiognomonia leptostyla (Fr.) Sogonov. The effectiveness of fungicides was the highest in the variant with the drug Kuproksat, hp, (on the leaves — 70.4%, on the fruits — 75.9%). Technical efficiency of the drug Medyan Extra 350 SC, s. c. on leaves and fruits was 64.6 and 67.9%, respectively. Fungicide treatment of experimental plots helps to reduce the incidence of the disease, which makes it possible to obtain a yield of 0.9—1.1 t/ha higher than in the control.